(untitled) (Bioscience Journal, 2023)
Rust is the main disease affecting Coffea arabica, the most economically important coffee species. The objective of this study was to analyze C. arabica cultivars with different levels of rust resistance, including bean size, raw bean appearance, final sensory scores (FSS), and aroma and taste nuances of the coffee cup. The experiment was designed in randomized blocks (RBD) with three replications and 20 treatments (cultivars), totaling 60 experimental plots. The rust-susceptible cultivars IPR 100, Rubi MG 1192, and Topázio MG 1190 were compared with 17 rust-resistant cultivars. Cultivars IPR 103, MGS Aranãs, and Saíra II presented the highest percentages of high sieves, highest scores of raw bean appearance, and low percentages of mocha-type beans. All cultivars had FSS above 82 and were classified as specialty coffees. The cultivars with the highest FSS (Arara and Catiguá MG2) showed a greater diversity of coffee cup aroma and flavor nuances. Rust-resistant Arabica coffee cultivars are promising for the physical quality of beans and have potential for the specialty coffee market.